Moral knowing, moral feeling, and moral action in reflecting moral development of students in junior high school - Purwati Purwati; Muhammad Japar; Laili Qomariyah; Fatwa Tentama (Institute of Advanced Engineering and Science, 2024)
This research objective is to test the validity and reliability of moral development instruments on junior high school students. The moral development instrument for junior high school students was developed based on three aspects of moral development: moral knowing, moral feeling, and moral action. This research sample involves 172 students at Junior High School “X” in Magelang City, Indonesia ranging from 12 to 15 years of age. The total items developed from the three aspects are 152 items consisting of 60 items of moral knowing, 62 items of moral feeling, and 30 items of moral action. The items analysis was calculated using the product moment correlation technique and corrected item-total correlation technique. This research result indicates that the moral development instrument is valid with the score of rcount>rtable and stated reliable with Cronbach alpha score of moral knowing is 0.876, moral feeling is 0.886, and moral action is 0.830. The validity and reliability test result shows that the moral development instrument for students is feasible to use. Moral knowing, moral feeling, and moral action can reflect students' moral development.